Trends in the veterinary clinic for pets in Guatemala city: Tendencias en la clínica veterinaria de mascotas en ciudad de Guatemala - Aguilar, Erika; Álvarez, Melissa; Vidaurre, Ramón; Rivera, Miguel; Lepe-López, Manuel (Universidad del Zulia p-ISSN 0798-2259; e-ISSN 2521-9715; l-ISSN 2477-944X, 2021)
Veterinary practice in Guatemala presents a change in the type of patients attended in consultation, contemplating an increase in pet care. However, an understanding of the trends involved in pet consultation is unknown in Guatemala. This study explores the flow of inquiries, owners, and pets at a veterinary clinic located in Guatemala City. A database compiled with the QVET software from April to December 2,019 was described. The number of owners by biological sex, the number of pets by species, sex, and the breed was estimated. The behavior of queries over time, the proportions of pets by sex and by species, and the association between the biological sex of the owner with the sex and with the species of the pet was explored. One thousand two hundred ninty owners (797 women and 493 men), 1,753 pets (931 females and 822 males) were identified, these being one thousand five hundred ninety and two of the species Canis lupus familiaris (842 females and 750 males) and 161 of the species Felis silvestris catus (89 females and 72 males). The number of consultations tends to decrease over time, in the months towards the end of the year. The female domestic dog is the most common pet among owners. There is an association between the biological sex of the owner and the biological sex of the pet (X-squared = 3.6619, df = 1, P-value = 0.05567) and between the biological sex of the owner and the animal species of the pet (X- squared = 3.7803, df = 1, P-value = 0.05186). According the obtained results, women wereassociated with female pets and domestic cats. The implications of these trends regarding the services and training of veterinarians to meet the demand for pet consultation in Guatemala are discussed. La práctica veterinaria en Guatemala presenta un cambio en el tipo de pacientes atendidos en consulta, contemplando un incremento en la atención de mascotas. No obstante, la comprensión de las tendencias involucradas en la consulta de mascotas es desconocida en Guatemala. El presente estudio explora el flujo de ...